Protective effects of Dimethyl malonate on neuroinflammation and blood-brain barrier after ischemic stroke. Issue 14 (6th October 2021) - Zhang, Zhen; Lu, Zhengfang; Liu, Chang; Man, Jiang; Li, Xiang; Cui, Kefei; Lu, Hong; Wang, Jianping
Abstract : Objectives: After ischemic stroke, microglia will be activated and play a key role in neuroinflammation and the destruction of the blood-brain barrier (BBB), and activated microglia could polarize into pro-inflammation M1 phenotype and anti-inflammation M2 phenotype. Dimethyl malonate (DMM) could reduce reactive oxygen species and we speculate DMM could regulate microglia to protect ischemic brain. Methods: We used transient middle cerebral artery occlusion (tMCAO) mouse model to simulate ischemic stroke and adult male C57BL/6 mice were used in our study. 2, 3, 5-triphenyltetrazolium chloride staining was used to measure infarct volume. Evans Blue and Brain water content were used to evaluate the destruction of BBB. We used a five-point scale to assess the neurologic function of mice. Western blot and Immunofluorescence were used to measure microglia, pericytes and the expression of related proteins. Results: DMM reduced cerebral infarct volume, Evans blue leakage, brain water content and improved neurologic deficits after tMCAO. The number of activated microglia and M1 microglia were decreased and the number of M2 microglia and pericytes were increased after DMM treatment. The expression of tumor necrosis factor-α was reduced while protein levels of IL-10 and ZO-1 were increased through DMM treatment. Conclusions: DMM could regulate activation and polarization of microglia to inhibit neuroinflammation and protect BBB.